Pemetaan Digital Literacy Competencies Guru Madrasah Aliyah di Bandar Lampung Pada Era Digital Native Generation - Eri Maryani; Ida Nurhaida; Nina Yudha Aryanti; Andi Windah; Arnila Purnamayanti (STKIP Al Islam Tunas Bangsa dan HEPI, 2023)
Students today are a digital native generation, which since birth have been surrounded and familiar with the development of ICT. So that this generation has different characters including learning styles. To be able to keep up with and follow the learning styles of students, a teacher is required to have skills in literacy, especially digital literacy. This study uses a qualitative descriptive approach and data collection using questionnaires, interviews, literature study, and triangulation. Furthermore, the determination of the sample using purposive sampling technique. Data were analyzed using a quantitative descriptive approach and deepened with qualitative analysis. The results of the research show that the digital literacy competencies of MA teachers in Bandar Lampung are seen from the categories, (1). Internet searching